BRANDING DODOL PRODUKSI UD. KEMAS SEBAGAI OLEH-OLEH KHAS KABUPATEN BENGKALIS - Ummi Aida Z.A; Andri Sulistyani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Branding is an activity to communicate, build up, and maintain a brand in order to put the perspective to other people who see it. However, branding itself is not limited to product differentiation, but is also related to trademarks, visual characteristics, credibility, perceptions, logos, images, impressions, characters and also the perceptions of consumers themselves about the product. This research aims to find out what are the stages of branding and how to implement the process of branding dodol produced by UD Kemas in such a way that it can become a unique souvenir of Bengkalis Regency. This research uses a qualitative method with a descriptive approach to describe the actual situation by collecting information data directly from the field. The key informants of this research are the founders and managers of UD Kemas, UD Kemas workers, consumers and the distributor itself. This research uses data collection techniques from literature study, observation, documentation and interviews. The results of this research is that the stages and implementation of branding carried out by UD Kemas can be considered good to such extend that there is a very good inflation in sales. Keywords: Branding, UD Kemas, Souvenirs, Bengkalis Regency.